Distinguishing IgG4-Related Ophthalmic Disease From Graves Orbitopathy. Issue 2 (March 2019) - Tooley, Andrea A.; Salomao, Diva R.; Bradley, Elizabeth A.; Garrity, James A.
Abstract : Purpose: The authors aimed to determine key features of IgG4-related ophthalmic disease (IgG4-ROD) and Graves orbitopathy (GO) to aid in diagnosis. Methods: The authors retrospectively identified ophthalmology patients seen between June 2009 and November 2013 with clinical overlap of GO and IgG4-ROD. Patient findings were reviewed to characterize the 2 conditions. Results: Among 8 patients (7 male and 1 female), the mean age was 45.8 years. Time between diagnoses of GO and IgG4-ROD ranged from 1 month to 8 years. Imaging showed enlarged extraocular muscles in all patients. Enlarged infraorbital nerves were seen in 4 patients. Tissue biopsy showed CD20+ lymphocytes with a large proportion of IgG4 plasma cells in 7 of 8 orbital specimens. Six patients had a ratio of IgG4:IgG cells >40%. Discussion: No pathognomonic clinical findings for GO or IgG4-ROD have been reported, but some key features can help distinguish the conditions. GO is likely if findings include increased thyrotropin receptor antibodies, lid retraction/lid lag, and enlarged extraocular muscles with typical tendon-sparing morphology. Findings suggestive of IgG4-ROD include history of asthma and progressive orbital disease in patients with previous diagnosis of GO, disproportionately large lateral rectus muscle, and enlarged infraorbital nerves. Increased serum IgG4 level and biopsy showing >10 IgG4+ plasma cells/high-power field and IgG4:IgG ratio >40% will support the diagnosis of IgG4-ROD. Conclusions: GO and IgG4-ROD are complicated inflammatory processes affecting the orbit and present diagnostic challenges. The authors recommend biopsy for patients who do not follow the usual clinical course of GO or have clinical characteristics of IgG4-ROD. Abstract : Although no pathognomonic findings have been reported for Graves orbitopathy or IgG4-related ophthalmic disease, this study of 8 patients with clinical overlap of these conditions identified several key features that may help clinicians distinguish them